COVID-19 and male infertility: An overview of the disease - Mohammed Imad Malki (9649555) (2022)
Since SARS-CoV-2 infection was first discovered in December 2019 in Wuhan City in China, it spread rapidly and a global pandemic of COVID-19 has occurred. According to several recent studies on SARS-CoV-2, the virus primarily infects the respiratory system but may cause damage to other systems. ACE-2, the main receptor for entry into the target cells by SARS-CoV-2, was reported to abundantly express in testes, including spermatogonia, Leydig and Sertoli cells. Nevertheless, there is no clinical evidence in the literature about whether SARS-CoV-2 infection has an impact on male reproductive health. Therefore, this review highlights the effect of SARA-CoV-2 infection on male reproductive health, including the reproductive system and its functioning, as well as gamete and male gonadal function that might be affected by the virus itself or secondary to immunological and inflammatory response, as well as drug treatments and the psychological stress related to panic during the COVID-19 outbreak. Other Information Published in: Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/md.0000000000029401